FORMAL VS INFORMAL CONTRACTS (NETWORKS) AND SUSTAINABILITY OF RASPBERRY FARMS IN WEST SERBIA – AN EXPLORATORY RESEARCH - Stojanović, Žaklina; Manić, Emilija; Janković, Irena (Economics of Agriculture, 2024)
Serbia has gained international recognition for its fruit production, particularly establishing itself as one of the top five global producers and exporters in the raspberry sector. Given the highly intensive nature of raspberry production and the diverse range of producers, spanning from small farms to large corporate entities, research on the sustainability of production and future strategies has become increasingly important. The study explores the significance of economic, environmental, and social factors influencing raspberry producers’ practices. It also delves into their future production strategies, examining these aspects from the perspective of farmers. The findings derived from interviews with farmers reveal statistically significant differences between the two subsamples, namely formal and informal, across basic socio-economic and sustainability indicators, as well as in their anticipated future production strategies. The specific approaches and measures in achieving overall sustainability were emphasised in the concluding remarks.